"In vitro" evaluation of the apical sealing of root canals obturated with different techniques Avaliação "in vitro" do selamento apical dos canais radiculares em função de diferentes técnicas de obturação - Viviane Haiub Brosco; Norberti Bernardineli; Ivaldo Gomes de Moraes (University of São Paulo, 2003)
The purpose of this study was to compare the apical sealing of root canals obturated with different techniques. One hundred-six human mandibular incisors were submitted to instrumentation by means of the step-back technique. After instrumentation, one hundred teeth received an impermeable coating on the external surfaces of the crown and root (except for the area nearby the apical foramen). Afterwards, they were divided in five groups containing twenty elements each, according to the obturation technique employed: 1. lateral condensation with Kerr file; 2. continuous wave of condensation technique with System B; 3. thermoplasticized injectable gutta-percha technique with the Ultrafil system; 4. mechanically thermoplasticized gutta-percha with the JS Quick-Fill system and 5. thermoplasticized gutta-percha associated to a master cone with the Microseal system. The six remaining teeth were employed as negative and positive controls. After obturation, the access cavities were sealed and the teeth were immersed in aqueous 2% methylene blue dye for 72 hours at 37ºC. After that, the teeth were longitudinally sectioned and the apical microleakage was evaluated in a stereomicroscope. The Microseal system presented the best apical sealing ability, followed by System B, JS Quick-Fill, Ultrafil and the lateral condensation technique. The statistical analysis of the results demonstrated that: 1. the Microseal system presented an apical sealing similar to System B and better than the other groups; 2. System B presented better apical sealing than the lateral condensation technique, being similar to the other groups; and 3. the lateral condensation, Ultrafil and JS Quick-Fill groups demonstrated similar sealing ability. Este estudo teve como objetivo avaliar o selamento apical de canais radiculares obturados por diferentes técnicas. Cento e seis incisivos inferiores humanos tiveram seus canais instrumentados através da técnica escalonada regressiva. Após a instrumentação, cem dentes foram impermeabilizados, exceto nas proximidades do forame apical, e divididos em cinco grupos de vinte elementos cada, de acordo com a técnica de obturação utilizada: 1. condensação lateral ativa realizada com lima tipo Kerr; 2. Onda Contínua de Condensação realizada com o System B; 3. guta-percha termoplastificada injetável realizada com o sistema Ultrafil; 4. guta-percha termoplastificada mecanicamente realizada com o sistema JS Quick-Fill; 5. guta-percha termoplastificada associada a um cone principal realizada com o sistema Microseal. Os seis dentes restantes foram utilizados como controles positivo e negativo. Após a obturação, os dentes foram imersos em solução aquosa de azul de metileno a 2%, durante setenta e duas horas, a 37ºC. A seguir, os dentes foram seccionados longitudinalmente e a infiltração apical avaliada em um estereomicroscópio. O sistema Microseal apresentou a melhor capacidade de selamento apical, seguido pelo System B, JS Quick-Fill, Ultrafil e pela técnica da condensação lateral. A análise estatística dos resultados demonstrou que: 1. o sistema Microseal apresentou selamento apical semelhante ao do System B e melhor que dos demais grupos; 2. o System B apresentou selamento apical melhor que o da técnica da Condensação Lateral e semelhante ao dos demais grupos; 3. os grupos da Condensação Lateral, Ultrafil e JS Quick-Fill, apresentaram capacidade de selamento semelhante.